Implementation of Problem Based Learning (PBL) Models to Improve Student Physics Learning Outcomes - Naenggolan, Rini Siti Suleh (Current STEAM and Education Research, 2023)
This study aims to determine the increase in student physics learning outcomes, teacher and student activities, the teacher's ability to manage learning, as well as student responses to the application of the Problem Based Learning (PBL) models in Newton's Law material during the learning process. This type of research is Classroom Action Research (CAR). The subjects in this study were class X students of one of senior high school in Pargodungan for the 2020/2021 academic year with a total of 29 students. Data collection instruments that researchers use in research are observation sheets, tests and questionnaires where the three data are analyzed with descriptive statistics. The results showed that (1) the percentage of individual completeness as a whole increased from cycle I to cycle III, namely 69%, 80%, and 94%, and the percentage of classical completeness as a whole also increased, namely 40%, 70%, and 80%; (2) there is an increase in teacher and student activity during the learning process; (3) there was an increase in the teacher's skills in managing learning from the fairly good category with an average of 2.59 to good with an average of 3.4; (4) student responses tended to be positive where 100% of students expressed pleasure in learning using this Constructivism-Problem Based Learning model. From this study it can be concluded that the application of the Problem Based Learning (PBL) Learning Model can improve the physics learning outcomes on Newton’s Law topic.